Development and Realisation of the Concept House 'Delft' Prototype - An Example of a Collaborative Concept Development for Energy Positive Apartments - A. van Timmeren (Research in Architectural Engineering Series, 2016)
The Delft Prototype is a single apartment from a not yet realized Concept House Urban Villa, which consists of 16 apartments on 4 floors. Both the urban villa and the prototype demonstrate the characteristics of high level industrial production with an extremely low ecological footprint, as well as being energy-positive in use, and both are suitable for multi-storey housing. The research, development, production and built prototype resulted in a unique innovation on the Dutch building market: a sustainable energy-positive apartment system for medium-rise energy-positive housing. This scientific report deals with the history, development and realization process of the prototype up to the completion of the building phase, after which the prototype was furnished and the garden landscaped, culminating with the opening of the prototype in October 2012. The development was initiated by Mick Eekhout's Chair of Product Development at the TU Delft at the specific request of the building industry and was carried out in close collaboration with a consortium of partners from the SME building supply industry. Innovation continues to progress in these partner industries. The entire project was externally financed for the 8 years of its duration. Apart from initiative and natural project leadership, the innovative contribution of the Chair included the design, coordination and integration of the many components into the single coherent entity of the Concept House 'Delft' Prototype.